2011
DOI: 10.1016/j.virol.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the epidermal growth factor receptor by erlotinib prevents immortalization of human cervical cells by Human Papillomavirus type 16

Abstract: The Human Papillomavirus type-16 (HPV-16) E6 and E7 oncogenes are selectively retained and expressed in cervical carcinomas, and expression of E6 and E7 is sufficient to immortalize human cervical epithelial cells. Expression of the epidermal growth factor receptor (EGFR) is often increased in cervical dysplasia and carcinoma, and HPV oncoproteins stimulate cell growth via the EGF-R pathway. We found that erlotinib, a specific inhibitor of EGFR tyrosine kinase activity, prevented immortalization of cultured hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…CXT cervical cancer cell lines and normal human cervical epithelial cells were isolated and cultured from tissue purchased from the Cooperative Human Tissue Network as described elsewhere [28]. Normal and CXT cancerous cells were cultured in Keratinocyte Serum‐Free Medium (KSFM) supplemented with 50 units/mL penicillin G, and 50 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…CXT cervical cancer cell lines and normal human cervical epithelial cells were isolated and cultured from tissue purchased from the Cooperative Human Tissue Network as described elsewhere [28]. Normal and CXT cancerous cells were cultured in Keratinocyte Serum‐Free Medium (KSFM) supplemented with 50 units/mL penicillin G, and 50 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The 3 early expression oncoproteins E5, E6, and E7 of highrisk HPV have complex interactions with the EGFR signaling pathway. The HPV-16 E6 and E7 oncoproteins 22,23 It has been shown that the disruption of EGFR inhibited development of papilloma and carcinoma from immortalized epithelial cells in mice. 9,24 Thus, the EGFR pathway is an important molecular target in cervical cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2). EGFR signaling is also needed for immortalization by either the HPV16 genome or E6/E7 alone 126 . The primary HPV protein that regulates EGFR signaling is E5.…”
Section: Growth Factorsmentioning
confidence: 99%